Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Dalam Penggunaan BSI Mobile Banking - Nurushofia, Ghaitsa; Salsabila, Putri; Yusuf, Mutiara Faizah; Saraswati, Heni; Hidayat, Wahyu (Maisyatuna, 2023)
At this time information and communication technology has developed rapidly. Therefore, BSI issued BSI Mobile, where the presence of BSI Mobile is expected to provide fast, safe and effective service to customers. Based on the explanation above, this study aims to determine how high the level of customer satisfaction is with the quality of BSI Mobile service users for customers who use BSI Mobile. This research was conducted based on a quantitative approach with causal research methods (Causal Study), where researchers will test hypotheses and look for the effect of independent variables on the dependent variable. Data collection was carried out by distributing questionnaires to 43 customer respondents using BSI Mobile. From the results of hypothesis testing it is known that service quality influences customer satisfaction in using BSI Mobile.